Sorting Characteristics of Black Soil Splash Erosion Aggregates Under Intermittent Rainfall Conditions - ZHANG Xiaoya; XU Jinzhong; YANG Qingnan; LEI Hanzhe; ZHAO Yikai; LI Yu; ZHANG Yupeng; FU Yu (Shuitu Baochi Xuebao)
[Objective] To investigate the impact of intermittent rainfall on the amount and sorting characteristics of black soil splash erosion. [Methods] This study is based on artificial simulated rainfall experiments, with two rainfall intensities (40, 70 mm/h) designed, each with 5 rainfall events, to analyze the splashing erosion amount and particle size distribution characteristics of black soil under different rainfall conditions. [Results] Under two different rainfall intensities, there is a dynamic development process of alternating strength between "no crust weak crust strong crust weak crust new crust" in the soil surface layer of different rainfall sites. Under two different rainfall intensities, the maximum values of splashed aggregate MWD and GMD appeared in the fourth rainfall, and the minimum values appeared in the first rainfall. The agglomerates with a particle size of 5～2 mm did not migrate in each rainfall, and the splashed agglomerates were mainly composed of particles with a size of 2～0.25 mm, accounting for 36.49%～58.61% and 49.10%～60.09% of the splashed erosion amounts of the two rainfall intensities, respectively. The erosion amount of the five rainfall events showed a trend of first increasing and then decreasing with the decrease of particle size, while the mass percentage with particle size <0.053 mm showed a trend of first decreasing and then increasing with the increase of intermittent frequency. The mass percentage with particle size <0.053 mm all showed the minimum value in the third rainfall event, which was 18.21% and 17.63%, respectively. [Conclusion] Rainfall can lead to the formation of soil crust, and the thickness of soil crust shows dynamic changes with the increase of rainfall frequency. In the third rainfall, the soil crust thickness is the highest, and at this time, the splash erosion amount has the minimum value, mainly greater than 0.053 mm. The research results provide reference for the study of soil water erosion mechanism in the black soil area of Northeast China.